Pengaruh Kadmium terhadap Gangguan Patologik pada Ginjal Tikus Percobaan - Anna Ratnaningsih (Jurnal Matematika Sains dan Teknologi, 2004)
Once of environmental pollution is heavy metal cadmium that causes toxic effect to the human and animal life. This research is to identify the effect of cadmium on kidney function. Cadmium was administered by adding it in drinking water. This study was performed by using four cadmium’s concentrations on drinking water which are 0 mg/L (control); 0.06 mg/L; 6.60 mg/L and 66.00 mg/L. Observation was conducted during 0 week; 2 week; 4 week; 6 week and 8 week. The failure of kidney function is indicated by accumulation of cadmium on the kidney and protein contens in the urin of Wistar rats. The result showed that the exposure of cadmium through drinking water caused pathophysiology effect in rats such as increasing of proteinuria and accumulation of cadmium in kidney. Pathological effect such as cell degeneration of kidney was also observed.